Knowledge, attitudes, behaviors, and information needs of women vaccinated with the HPV vaccine regarding cervical cancer prevention: a cross-sectional study - Zhou, Xuan; Wu, Miaomiao; Zhou, Yuling; Su, Fang; He, Yiqing; Ding, Jinxia; Xie, Lunfang (Frontiers in Public Health, 2025)
BackgroundCervical cancer poses a serious threat to women’s health globally, especially in China. HPV vaccination and screening are crucial prevention and control measures. However, the screening coverage among Chinese women remains low, and there is a need to better understand the knowledge, attitudes, behaviors, and information needs of Chinese HPV-vaccinated women regarding cervical cancer prevention to optimize prevention and control strategies.ObjectivesTo explore the knowledge, attitudes, behaviors, and information needs of women vaccinated with the HPV vaccine regarding cervical cancer prevention.MethodsThis cross-sectional study was conducted using a convenience sampling method from October 1 to December 30, 2023. A questionnaire survey was administered to 439 women vaccinated with the HPV vaccine at the Shu Shan District Community Health Service Center in Hefei, Anhui Province. The survey tool was self-designed. Data were analyzed using descriptive statistics, chi-square tests, and binary logistic regression.ResultsThe average age of the 439 participants was 27.82 ± 6.42 years. The average cervical cancer prevention knowledge score was 35.01 ± 5.76. 434 (98.9%) women held a positive attitude towards cervical cancer screening, and 320 (72.9%) women had undergone cervical cancer screening after receiving the HPV vaccine. Educational levels such as college (OR = 2.995, 95%CI: 1.233–7.279, p = 0.015), bachelor’s degree (OR = 3.694, 95%CI: 1.718–7.943, p = 0.001), and postgraduate and above (OR = 4.826, 95%CI: 2.176–10.707, p < 0.001), as well as occupation as medical workers (OR = 4.660, 95%CI: 2.292–9.474, p < 0.001), were associated with higher knowledge of prevention and treatment scores. Individuals aged 26–35 years (OR = 7.431, 95%CI: 2.856–19.331, p < 0.001), 36–45 years (OR = 11.466, 95%CI: 2.279–57.694, p = 0.003), married individuals (OR = 4.307, 95%CI: 1.455–12.750, p = 0.008), and participants who had received health education related to cervical cancer prevention (OR = 2.125, 95%CI: 1.169–3.863, p = 0.013) and possessed good knowledge of prevention (OR = 16.770, 95%CI: 8.667–32.451, p < 0.001) were more inclined to undergo cervical cancer screening. Among the 254 participants who had received health education, 34.2% still had unmet information needs regarding cervical cancer prevention, and 29.5% hoped to receive health education services from professionals.ConclusionChinese HPV-vaccinated women have a good understanding of cervical cancer prevention and a positive attitude and behavior towards cervical cancer screening. However, their knowledge of cervical cancer screening is not sufficient, and their information needs have not been fully met.